INNOVATIVE TECHNOLOGIES IN PEDIATRIC SURGERY: CLINICAL APPLICATIONS, EDUCATIONAL IMPACT, AND SOCIAL IMPLICATIONS - Agnieszka Walczak; Magdalena Domisiewicz; Kacper Domisiewicz (International Journal of Innovative Technologies in Social Science, 2026)
Background: Rapid technological progress has significantly transformed pediatric surgery, introducing innovative tools that influence not only clinical outcomes but also education, healthcare organization, and the social experience of patients and their families. Objective: This narrative review aims to synthesize current evidence on innovative technologies used in pediatric surgery, with particular emphasis on their clinical applications, educational value, and broader social implications. Methods: A comprehensive literature review was conducted using major scientific databases, including PubMed, Scopus, and Web of Science. Peer-reviewed articles published between 2015 and 2025 were analyzed, focusing on technologies such as three-dimensional (3D) printing, robotic-assisted surgery, augmented and virtual reality (AR/VR), simulation-based training, artificial intelligence (AI), and telemedicine. Results: Innovative technologies have demonstrated substantial benefits in pediatric surgery, including improved preoperative planning, enhanced surgical precision, reduced perioperative stress, and better training outcomes for surgeons. Three-dimensional printing and AR/VR facilitate personalized surgical planning and family education, while robotic platforms and AI-based tools offer potential improvements in minimally invasive procedures and decision-making. Simulation-based training contributes to patient safety, and telemedicine supports postoperative care and continuity of treatment. Conclusions: Innovative technologies are reshaping pediatric surgery beyond technical performance, affecting social, educational, and ethical dimensions of care. Future research should focus on long-term outcomes, cost-effectiveness, and equitable access to technological advancements.